Educational mediation applied with students about environmental health - doi: 10.4025/actascihealthsci.v35i1.10042 - Eveline Pinheiro Beserra; Maria Dalva Santos Alves; Raquel Maria Rigotto (Universidade Estadual de Maringá, 2012)
To describe an educational action applied by nurses about environmental health at a school. This is a research-action study carried out at a public school of Ceará State, in 2009. A group approach was accomplished with pictures triggering discussions. For this dialogue, concerning time and space, the pictures were culture tokens proposed by the students, completely within the context and relevant to the investigation. It was observed that the environmental health, in their conception, is a healthy nature, free of contaminations, and they also reported the connection between environmental health and people's mental well-being. They had brought pictures that showed natural elements from where they live, demonstrating the value of their productive land. The correlation between nurse and school is increasingly frequent in the health area, corresponding to a space that favors the use of interdisciplinary techniques to explore educational actions addressed to respond specific demands.